Public libraries and popularisation of science - Vrana, Radovan (2010)
The purpose of this paper is to present the ﬁndings from the research carried out among the directors of Croatian public libraries about cooperation between public libraries and the academic community and about promotion of science in Croatian public libraries. Owing to their number, strategic position in society and the skills and knowledge of librarians, public libraries have an opportunity to cooperate more intensively with the scientiﬁc community, expand their holdings with science-related content and to offer new services. Some already cooperate with the Croatian scientiﬁc community by participating in joint research projects and in promoting science. Although cooperation with the scientiﬁc community is not among their priorities, Croatian public libraries are enthusiastic to continue with this type of activity.
Projekt MZOS
ENG